Comparative cost-effectiveness analysis of CDK4/6 inhibitors in the first-line treatment of HR-positive and HER2-negative advanced breast cancer: a Markov's model-based evaluation - Elazzazy, Shereen; Al-Ziftawi, Nour Hisham; Mohamed Ibrahim, Mohamed Izham; Bujassoum, Salha; Hamad, Anas (Frontiers in Oncology, 2024)
Introduction: CDK4/6 inhibitors are the first-line treatment for HR+/HER2-advanced breast cancer. Despite their clinical benefit, they can increase healthcare expenditure. To date, there is no thorough comparison among the three approved CDK4/6 inhibitors in terms of their cost-effectiveness. Objective: To investigate and compare the cost-effectiveness of CDK4/6 inhibitors in combination with letrozole as a first-line treatment for advanced breast cancer with hormonal-receptor-positivity and HER-2negativity versus one another and versus letrozole monotherapy. Methods: A 10-year within-cycle-corrected Markov's model was employed from the healthcare payer perspective. Costs were obtained from the National Center for Cancer Care and Research (NCCCR) in Qatar. Utilities and transition probabilities were calculated from published landmark trials of PALOMA-2, MONALEESA-2, MONARCH-3, PO25, and other relevant literature. Costs, measured in Qatari Riyal (QAR), and effectiveness, measured in quality-adjusted-life-years (QALYs), were incremented and the incremental cost-effectiveness ratio (ICER) was compared to a willingness-to-pay threshold (WTP) of 1.5 Qatari GDP (448,758 QAR). A deterministic sensitivity analysis was implemented to account for uncertainties. Results: Ribociclib was the most effective option, generating 4.420 QALYs, followed by palbociclib (4.406 QALYs), abemaciclib (4.220 QALYs), then letrozole monotherapy (2.093 QALYs). As for cost-effectiveness, ribociclib dominated palbociclib. However, it was not cost-effective compared to abemaciclib (ICER=1,588,545 QAR/QALY). Ribociclib remained dominant over palbociclib with all uncertainties. The base-case conclusion of ribociclib versus abemaciclib remained robust over all uncertainties. Conclusion: From the healthcare payer perspective in Qatar, ribociclib is the most effective CDK4/6 inhibitor. It was dominant over palbociclib in terms of cost-effectiveness; however, it was not cost-effective compared to abemaciclib at current prices.